Biomechanical Testing of Scapular Spine Autograft for Anterior Glenoid Bone Augmentation. Issue 5 (13th May 2022) - Mittelsteadt, Marcus; Nelson, Bradley J.; Rohman, Eric M.; Arciero, Robert A.; Tompkins, Marc A.
Background: Augmentation of anterior glenoid defects with bone graft can improve shoulder stability and reduce the risk of redislocation. Several characteristics of the scapular spine may make it a suitable harvest site, avoiding the disadvantages associated with other glenoid augmentation procedures. Purpose: To evaluate the capacity of scapular spine autograft to restore the stabilizing joint-reaction forces of the shoulder in simulated scenarios of bony anterior shoulder instability. Study Design: Controlled laboratory study. Methods: We obtained 6 matched pairs of fresh-frozen cadaveric shoulders. Skin, subcutaneous tissues, and non–rotator cuff muscles were removed from the specimens, leaving intact the rotator cuff musculature and shoulder capsule. A customized testing device was used to translate the humerus 1 cm anteriorly on the glenoid under 25 N of axial compression force. The peak joint-reaction force of the glenohumeral joint was then measured under 3 conditions: (1) specimen with intact glenoid, (2) specimen after a bone defect measuring 25% of the maximal width of the glenoid was made in the anteroinferior glenoid, and (3) specimen after size-matched glenoid augmentation with a scapular spine tricortical autograft. The primary outcome was the change in peak joint-reaction forces between the defect state and augmented state. Results: One matched pair was removed from final analysis secondary to anatomic concerns that undermined the accuracy of test results. Among the 10 remaining specimens, all showed a significant decrease in peak joint-reaction force after the glenoid defect was created compared with the intact state ( P < .001). All remaining specimens showed an increase in peak joint-reaction force in the augmented state compared with the defect state ( P < .001). On average, the augmented state restored 81% of the peak reaction force of the glenohumeral joint compared with the intact state, a nonsignificant difference ( P = .07). Conclusion: The study findings indicated that autograft harvested from the scapular spine increased the bony restraint to anterior shoulder dislocation in shoulders with glenoid bone loss. Clinical Relevance: The scapular spine is an alternative for bony augmentation of glenoid defects in shoulder instability.